Perancangan Tipografi Adaptasi dari Ornamen Motif Ulos Sadum Mandailing - Rendy Prayogi; Mhd Rusdi Tanjung; Hafidz Alwi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Communication is the most important activity in everyday life, language and writing are effective communication tools both verbally and visually, communication in a visual context will be conveyed through typography. As time and technology develop, typography plays an important role and presents many types and styles of letters almost every day which have their own characteristics and uniqueness, one of which is the modern typeface which has minimalist and geometric shapes as benchmarks. The design of this modern typeface typography aims to create letters, numbers and punctuation characters that have their own uniqueness and characteristics by exploring the potential shapes that exist in the Ulos Sadum Mandailing motif ornaments.